Evaluating the synergy: anxiety prevalence and alcohol consumption patterns in high-income countries using Granger causality analysis - Binguni Senarathne; Dinithi Palliyaguru; Anne Oshini; Janudi Gamage; Ruwan Jayathilaka; Lochana Rajamanthri; Colinie Wickramarachchi (BMC Public Health)
Abstract Background Alcohol consumption frequently experiences episodes of severe anxiety. This study set out to explore the long-term effects of alcohol consumption on anxiety, revealing insights into how alcohol consumption uniquely impact anxiety, aiming to inform mental health and public health approaches. This research paper explores the complex relationship between the prevalence of anxiety and the consumption patterns of wine, beer, and spirits across fifty-two high-income countries with a continental analysis. Method By employing significant secondary data taken from the World Health Organization and Our World in Data online databases and covering the period from 1990 to 2019, this study seeks to explore various causality relationships over this period. Its primary objective is to fill the empirical gap in existing research by using Granger causality analysis to reveal the dynamic relationships between the consumption of alcohol and the prevalence of anxiety. This study endeavours to provide a continental analysis of the high-income countries, which allows for including a comprehensive viewpoint in the context of a single investigation. Results The findings demonstrate a variety of patterns of causality in alcohol consumption and anxiety prevalence in a one-way causal relationship across specific continents, a bidirectional relationship in others, and no apparent causal relationship in several countries. Conclusion The inference made from the study’s results goes beyond scholarly curiosity; it establishes the foundation for further investigations and the development of customised policies aimed at reducing the mutually reinforcing dangers of alcohol consumption and anxiety disorders.